SHORT CONSIDERATIONS ABOUT THE PROTOCOL ON THE CROSS-BORDER COOPERATION IN THE EUROREGION "SIRET-PRUT-NISTRU" BETWEEN ROMANIA AND REPUBLIC OF MOLDOVA - Tudor Florin (European Regional Science Association (ERSA), 2010)
The idea of a Europe of regions has appeared in Western Europe in the 60s. Also in the 60s the first cooperation between neighboring regions created on the borders of France, Switzerland and Germany. The opportunities of the economic development with future EU Member States should not be ignored, as prerequisites of good neighborly relations in the border territories, the coordination of policies of mutual interest, the solution to the specific problems of the people near border as taxation, social security, workers border and establish institutional structures for cooperation. The purpose of this article is to identify the common interest points regarding foreign trade policy, quantitative restrictions and trade bans in the relationship with Moldova, as a starting point in establishing a new strategy to promote cross-border cooperation protocol Euroregion "SIRET-PRUT-NISTRU"
Keywords: F40; F36; K34; E62; 330; border cooperation; Euro region; regional development programs